PENDAMPINGAN INSTRUCTIONAL LEADERSHIP BAGI KEPALA SEKOLAH PADA PROGRAM SEKOLAH PENGGERAK DI KABUPATEN WAJO - Yulianto, Harry (Nindikayla Institute, 2023)
The role of the headmaster in the mover school program was crucial. The part of instructional leadership to increase teacher professionalism was a major factor in schools. This activity aims to make the headmaster understand instructional leadership's ability to improve teacher professionalism. The mentoring activities were conducted face-to-face and attended by the headmaster at the elementary school at the mover school program in Wajo Regency. Implementing the action uses assistance with lecture, discussion, and practice techniques. The data analysis techniques used descriptive statistics. The results of the activities: (1) implementation of mentoring activities, (2) most participants have a high level of ability to absorb knowledge and apply the concept of instructional leadership, and (3) the mentoring results positively impact the headmaster in preparing actual action plans. Recommendations for the results of the implementation of the activities were: (1) headteachers to conduct periodic reflections in their schools, (2) headmaster to optimize the community of practitioners, and (3) headmaster to carry out continuous training to improve competency and professionalism of teacher.